Udział obywateli w procedurze ustawodawczej w Republice Federalnej Niemiec - Malicka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
According to Article 20 of the Basic Law, the Federal Republic of Germany is a democratic, social, and federal state in which all power comes from the people and is exercised by them through elections and votes. In practice, voting, which is to be understood as an instrument of direct democracy, applies only to the new territorial division of the Länder. The instruments of direct democracy are more widely used in lawmaking in the individual Länder. Among other things, the law provides for citizens’ legislative initiative. This would require an amendment to the Basic Law if federal law were to be passed. To date, proposals for such amendments have been rejected.
Keywords: legislative procedure; Bundestag; direct democracy; representative democracy; legislative initiative; referendum